2008
DOI: 10.1007/s00431-008-0844-5
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the blood glucose level in perinatal asphyxia

Abstract: The severity of encephalopathy and cellular damage varies with the severity of hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 11 publications
2
45
0
5
Order By: Relevance
“…Neonates with NE caused by HIE are at increased risk of depleting their energy stores and developing concurrent hypoglycemia. 4 When caring for infants with NE, is it important to identify the etiology and time of the brain injury and to predict neurodevelopmental outcome. 5,6 Neuroimaging with MR has been shown to be the ideal tool to demonstrate the extent of injury and predict outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neonates with NE caused by HIE are at increased risk of depleting their energy stores and developing concurrent hypoglycemia. 4 When caring for infants with NE, is it important to identify the etiology and time of the brain injury and to predict neurodevelopmental outcome. 5,6 Neuroimaging with MR has been shown to be the ideal tool to demonstrate the extent of injury and predict outcome.…”
mentioning
confidence: 99%
“…[12][13][14] These studies also suggest that lower glucose levels are associated with a higher severity of encephalopathy and a worse outcome at 2 years. 4,14 Neuroimaging studies in neonatal hypoglycemia have shown a correlation between hypoglycemia, parieto-occipital injury, and involvement of the underlying white matter tracts, corpus callosum, and thalamus. 8,15,16 However, it is unclear whether the pattern of injury seen in HIE is modified by concurrent hypoglycemia and whether the effects of hypoglycemia in the context of HIE can be reliably recognized by imaging alone.…”
mentioning
confidence: 99%
“…52 Establishment of cerebral isoelectricity may be asynchronous, and this may explain asymmetric lesions in a given patient. 9,46 Contrary to the above observations, Schmidt et al 11 recently…”
mentioning
confidence: 82%
“…Hypoglycemia potentiates hypoxia-induced damage, and a combination of the 2 leads to worse outcomes than hypoxia alone. 4,46,47 These children often present with nonspecific symptoms such as seizures, lip-smacking, poor feeding, hypotonia, cyanosis, and vomiting. 4 There is scarce literature on perfusion imaging and spectroscopy findings in these patients.…”
Section: Neonatal Hypoglycemiamentioning
confidence: 99%
“…En caso de hematocrito bajo el rango se corregir con transfusión de glóbulos rojos en alícuotas de 15 ml/kg. la hipoglicemia es un marcador de mal pronóstico, incluso más que el Apgar y la acidosis, por lo cual es fundamental mantener desde un comienzo glicemia estable entre 75-100 mg% [16][17] .…”
Section: Terapia De Rescateunclassified